Estimation of Nutritive Value of Spring Alfalfa–Grass Mixtures using In‐Field Measurements and Growing Degree Data. Issue 1 (1st December 2013) - Parsons, David; Peterson, Paul R.; Cherney, Jerome H.
Abstract : Rapid estimation of forage nutritive value can help producers manage time of harvesting for mixed alfalfa–grass stands. In New York State, equations have been developed for neutral detergent fiber (NDF) estimation; however, other measures of nutritive value may be favored by some producers. Equations were developed to estimate spring growth nutritive value of mixed stands of alfalfa–grass in New York State using easily available measurements. There was a strong relationship between NDF derived from wet chemistry and near infrared spectroscopy (NIRS) for both grass and alfalfa fractions. For NDF, acid detergent fiber (ADF) and relative feed value (RFV), models incorporating the fraction of grass in the sample (GFRAC) and the maximum alfalfa height (MAXHT, inches) had the greatest predictive accuracy. For NDF digestibility (NDFD) and relative forage quality (RFQ), models incorporating growing degree days (GDD) had the greatest predictive accuracy, although further evaluation is necessary.